2014
DOI: 10.2215/cjn.06550613
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence, Awareness, and Management of CKD and Cardiovascular Risk Factors in Publicly Funded Health Care

Abstract: Background and objectives It is uncertain how many patients with CKD and cardiovascular risk factors in publicly funded universal health care systems are aware of their disease and how to achieve their treatment targets.Design, setting, participants, & measurements The CARTaGENE study evaluated BP, lipid, and diabetes profiles as well as corresponding treatments in 20,004 random individuals between 40 and 69 years of age. Participants had free access to health care and were recruited from four regions within t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
45
1
3

Year Published

2015
2015
2020
2020

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 55 publications
(51 citation statements)
references
References 35 publications
2
45
1
3
Order By: Relevance
“…While we cannot directly apply this factor to current national estimates of awareness, our data suggest that CKD awareness may have exceeded the Healthy People 2020 target of 13.4% (2). However, CKD awareness remains lower than awareness of diabetes and hypertension (32). Similar to CKD, diabetes and hypertension are often asymptomatic yet still require active patient selfmanagement, including daily medication adherence.…”
Section: Discussionmentioning
confidence: 99%
“…While we cannot directly apply this factor to current national estimates of awareness, our data suggest that CKD awareness may have exceeded the Healthy People 2020 target of 13.4% (2). However, CKD awareness remains lower than awareness of diabetes and hypertension (32). Similar to CKD, diabetes and hypertension are often asymptomatic yet still require active patient selfmanagement, including daily medication adherence.…”
Section: Discussionmentioning
confidence: 99%
“…We excluded three with a known history of renal disease. The remaining 943 were 5469 years old, with 51% women and a body mass index (BMI) of 26 (23)(24)(25)(26)(27)(28)(29)(30) (Table 1); 83% were white, 5% had a parent from Africa, 1% had a parent from Latin America, 4% had a parent from the Middle East, 2% were Asian, and 5% were from another descent. Cardiovascular risk factors and history were prevalent: 28% reported hyperlipidemia, 17% reported hypertension, 11% reported diabetes, and 6.7% had a history of coronary artery disease or stroke.…”
Section: Cohort Characteristicsmentioning
confidence: 99%
“…Another study among Hispanic/Latinos in the USA also reported only 29.5% patients with dyslipidaemia were receiving lipid lowering treatment 8. Furthermore, a study in Canada among patients with moderate to high Framingham risk scores found that many of them were not receiving a statin 9. A local study, using the Pooled Cohort Risk Score in primary care patients to identify the need for statins, reported that there was both underuse of statin therapy in those who required it and overuse of statins in those who did not qualify for it 10.…”
Section: Introductionmentioning
confidence: 99%